2019
DOI: 10.3389/fvets.2019.00285
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the LeadCare® Plus for Use on Scandinavian Brown Bears (Ursus arctos)

Abstract: Lead (Pb) exposure is associated with adverse health effects in both humans and wildlife. Blood lead levels (BLL) of sentinel wildlife species can be used to monitor environmental lead exposure and ecosystem health. BLL analyzers, such as the LeadCare®, are validated for use in humans, assessed for use in some avian species and cattle, and are increasingly being used on wildlife to monitor lead exposure. The LeadCare® analyzers use a technique called anodic stripping voltammetry (ASV). Species-specific convers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 47 publications
1
8
0
Order By: Relevance
“…Brown bears ( Ursus arctos ) did show elevated lead levels in this landscape, but lead levels did not increase during the hunting season (Rogers et al, 2012). In contrast, brown bears sampled in northern Europe have shown markedly elevated lead levels in blood and milk (Boesen et al, 2019), and lead levels in the teeth of Canadian black bears increase markedly during hunting seasons (Brown et al, 2022). It is clear that further research is required into risk factors for harmful lead exposure in free ranging mammalian species (Chiverton et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Brown bears ( Ursus arctos ) did show elevated lead levels in this landscape, but lead levels did not increase during the hunting season (Rogers et al, 2012). In contrast, brown bears sampled in northern Europe have shown markedly elevated lead levels in blood and milk (Boesen et al, 2019), and lead levels in the teeth of Canadian black bears increase markedly during hunting seasons (Brown et al, 2022). It is clear that further research is required into risk factors for harmful lead exposure in free ranging mammalian species (Chiverton et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The exception to this trend has been studies of bears (Ursus spp.) in the Northern Hemisphere (Boesen et al, 2019;Brown et al, 2023Brown et al, , 2022Fuchs et al, 2021). One recent study from the Southern Hemisphere demonstrated harmful lead levels in an Australian marsupial species, the Tasmanian devil (Sarcophilus harrisii), when fed whole shot carcasses in captivity (Hivert et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…and bears ( Ursus arctos ). Bears often dominate gut pile resources ( Rogers et al., 2012 ; Legagneux et al., 2014 ) and have been identified as highly exposed to environmental Pb ( Boesen et al., 2019 ). The relationship between mammalian exposure and scavenging is yet to be fully explored despite a direct link between toxicosis and scavenging behaviour in raptors and corvids ( Mee and Snyder, 2007 ; Legagneux et al., 2014 ; Golden et al., 2016 ; Pain et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the lead concentration in blood can be determined on-site using commercially available portable ASV-based analysers 134 . This enables a lead exposure assessment of children 135 , lead miners and smelters 133 and wild animals 136,137 . New ASV procedures continue to be developed and applied for determination of copper, lead, cadmium or zinc using new sensors, configurations and procedures 19,39,40,57,[138][139][140] .…”
Section: Trace Metals and Metalloidsmentioning
confidence: 99%